Clogging susceptibility study of drip emitters - BIJU A. GEORGE; E. B. Gilsha Bai; S. Rini Rani; Roy Tharakan; Er. E. K Kurien (Guide) (Tavanur 1993 Department of Irrigation University and Drainage Engineering)
Clogging susceptibility study of drip emitters
Clogging susceptibility study of drip emitters